Managerial attitudes and the leadership styles of university librarians in the Philippines - Cichon, Melchor F.; Atienza, Daisy B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1986)
The objectives of this study are two-fold: 1) to describe the demographic characteristics of university librarians; and 2) to identify the managerial attitudes and leadership styles of the university librarians.
Of the 60 university librarians who were sent the questionnaires, 34 or 56.66 percent responded. With librarian as the unit of analysis, the statistical tools used were mean, percentage, Fisher Exact Probability Test, and test of Two Proportions.
The profile of the respondents showed that 85 percent were females; 70.59 percent, between 32 to 50 years old; 79.41 percent, married; 64.71 percent are from the rural areas; and 70.59 percent are permanently residing in the cities. The majority of respondents (55.87 percent) are from Luzon; 26.47 percent, from the Visayas; and 17.65 percent, from Mindanao.
As for ethnic groupings, 44.12 percent are Visayans (Cebuano, Ilonggo and Waray), 47.06 percent are from Luzon (Tagalog, Bicolano, Ibanag, Pampango); one is a Muslim; and another one, an American.The majority (58.82 percent) masteral degrees; 35.29 percent, baccalaureatte degrees. Only 14.70 percent had no units in any masteral degree.
Of the 54 institutions that produced university librarians in the Philippines, the University of San Carlos topped the list with 23.52 percent, followed by the University of the Philippines with 17.64 percent.
The majority (52 percent) of the respondents received their degrees before 1971. One half of the respondents had served as university librarians for less than ten years.
The majority (52.92 percent) supervised about twenty personnel. The lowest number of supervised staff was 3, and the biggest number of personnel was 195, reported by the University of the Philippines Library System. Those libraries with a limited staff employed student assistants.
The majority of the respondents showed "modern" managerial attitudes on the following: capacity for initiative, assuming leadership roles, providing incentives, exerting influence, allowing group decision making, and cultivating harmony. They showed "classical" management attitudes on clarifying task direction and sharing information.
The university librarians exercised democratic leadership style in defining objectives, making a plan, communicating, controlling progress, evaluating results, building the work team, and developing individuals. None of the respondents showed any laissez-faire leadership style in developing individuals.
The Test of two Proportions showed that the greater the number of masteral degree holders, the greater the number of managers with democratic leadership style. In short, the higher the educational attainment of the managers, the more democratic their leadership style.
Aside from educational attainment, no significant relationships were established between democratic leadership style and other variables under study.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: College librarians--Philippines.; Leadership; Management